On history and policy: Time in the age of neoliberalism - Francesco Boldizzoni (Max Planck Institute for the Study of Societies, 2013)
It is often said that history matters, but these words are often little more than a hollow statement. In the aftermath of the Great Recession, the view that the economy is a mechanical toy that can be fixed using a few simple tools has continued to be held by economists and policy makers and echoed by the media. The paper addresses the origins of this unfortunate belief, inherent to neoliberalism, and what can be done to bring time back into public discourse. – – Es heißt, dass Geschichte wichtig sei, aber oft ist dies nicht mehr als eine Redensart. Ökonomen und Politiker halten mit Unterstützung der Medien auch nach der Großen Rezession an der Ansicht fest, dass die Wirtschaft ein mechanisches Spielzeug ist, das mit ein paar einfachen Werkzeugen repariert werden kann. In dem vorliegenden Papier betrachtet der Autor die Ursprünge dieses dem Neoliberalismus innewohnenden Irrglaubens und untersucht, wie geschichtlich-zeitliche Zusammenhänge zurück in den öffentlichen Diskurs gebracht werden können.
Keywords: 300